Correlates of protection for enteric vaccines. Issue 26 (8th June 2017) - Holmgren, Jan; Parashar, Umesh D.; Plotkin, Stanley; Louis, Jacques; Ng, Su-Peing; Desauziers, Eric; Picot, Valentina; Saadatian-Elahi, Mitra
Abstract: An immunological Correlate of Protection (CoP) is an immune response that is statistically interrelated with protection. Identification of CoPs for enteric vaccines would help design studies to improve vaccine performance of licensed vaccines in low income settings, and would facilitate the testing of future vaccines in development that might be more affordable. CoPs are lacking today for most existing and investigational enteric vaccines. In order to share the latest information on CoPs for enteric vaccines and to discuss novel approaches to correlate mucosal immune responses in humans with protection, the Foundation Mérieux organized an international conference of experts where potential CoPs for vaccines were examined using case-studies for both bacterial and viral enteric pathogens. Experts on the panel concluded that to date, all established enteric vaccine CoPs, such as those for hepatitis A, Vi typhoid and poliovirus vaccines, are based on serological immune responses even though these may poorly reflect the relevant gut immune responses or predict protective efficacy. Known CoPs for cholera, norovirus and rotavirus could be considered as acceptable for comparisons of similarly composed vaccines while more work is still needed to establish CoPs for the remaining enteric pathogens and their candidate vaccines. Novel approaches to correlate human mucosal immune responses with protection include the investigation of gut-originating antibody-secreting cells (ASCs), B memory cells and follicular helper T cells from samples of peripheral blood during their recirculation.